Development of allele-specific primer PCR for a swine TLR2 SNP and comparison of the frequency among several pig breeds of Japan and the Czech Republic - Muneta, Yoshihiro; Minagawa, Yu; Kusumoto, Masahiro; Shinkai, Hiroki; Uenishi, Hirohide; Splichal, Igor (The Journal of veterinary medical science, 2012)
In the present study, we have developed an allele-specific primer-polymerase chain reaction (ASP-PCR) for genotyping a single nucleotide polymorphism (SNP) of swine Toll-like receptor 2 (TLR2) (C406G), which is related to the prevalence of pneumonia caused by Mycoplasma hyopneumoniae. We also compared the allele frequency among several pig breeds of Japan and the Czech Republic. Allele-specific primers were constructed by introducing 1-base mismatch sequence before the SNP site. The swine TLR2 C406G mutation was successfully determined by the ASP-PCR using genomic DNA samples in Japan as previously genotyped by a sequencing method. Using the PCR condition determined, genomic DNA samples from pig blood obtained from 110 pigs from 7 different breeds in the Czech Republic were genotyped by the ASP-PCR. The genotyping results from the ASP-PCR were completely matched with the results from the sequencing method. The allele frequency of the swine TLR2 C406G mutation was 27.5% in the Czech Republic and 3.6% in Japan. The C406G mutation was only found in the Landrace breed in Japan, and was almost exclusively found in the Landrace breed in the Czech Republic as well. These results indicated the usefulness of ASP-PCR for detecting a specific SNP for swine TLR2.
Keywords: alely; Polymorphism, Single Nucleotide; Breeding; DNA primery; Japonsko; Toll-Like Receptor 2; jednonukleotidový polymorfismus; genomika; Alleles; chov; zvířata; Japan; Swine; DNA; toll-like receptor 2; polymerázová řetězová reakce; Czech Republic; DNA Primers; Polymerase Chain Reaction; Animals; Česká republika; Genomics; prasata